Achievement Motivation of Employees of PT. Bank Rakyat Indonesia (PERSERO) Tbk Bengkulu Branch Office - Lydia Gustina Putri (Penerbit Jurnal Indonesia, 2021)
This study want to describe achievement motivation of employees’ in the PT. Bank Rakyat Indonesia (BRI) tbk branches Bengkulu. Achievement motivation of employees’ are viewed from the side of cognition, affection, and conation. This study adopt the motive scale from McClelland theory of motivation, namely achievement motive and need for achievement. Result from descriptive analysis find that achievement motivation of employees’ in the PT. BRI branches Bengkulu is high. This result indicated that employees’ have perform their job very well.